2011
DOI: 10.1007/s10926-011-9345-x
|View full text |Cite
|
Sign up to set email alerts
|

Work Reintegration and Cardiovascular Disease: Medical and Rehabilitation Influences

Abstract: Medical reassurance can be an important influence on worker representations of disease threat. Medical advice as it pertained to work activities was less valued as it lacked considerations of work conditions. Cardiac rehabilitation lacked intensity and relevance to work demands. Occupational health was reassuring for workers and played an important role in developing return to work plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…Positive Return to Work (RTW) improves patients' quality of life, economic security and psychological health, and, in terms of increased productivity and cost reductions, it has financial benefits for the society [3][4][5][6]. However, RTW after a long-term sick leave may be stressful and emotionally demanding because it can be associated with patients' reduced physical capacities or changes in their work employment, such as reduction in working hours or in job tasks, decrease in self-reported responsibility and involvement [7][8][9]. Several studies have investigated the health-related qua lity of life (HRQL) after cardiac interventions [10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Positive Return to Work (RTW) improves patients' quality of life, economic security and psychological health, and, in terms of increased productivity and cost reductions, it has financial benefits for the society [3][4][5][6]. However, RTW after a long-term sick leave may be stressful and emotionally demanding because it can be associated with patients' reduced physical capacities or changes in their work employment, such as reduction in working hours or in job tasks, decrease in self-reported responsibility and involvement [7][8][9]. Several studies have investigated the health-related qua lity of life (HRQL) after cardiac interventions [10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by O'Hagan et al . (), key roles to enhance cardiac patients' feeling of personal control and adaptive illness beliefs are played by physicians, psychologists and occupational health personnel, resulting also in better work adjustment and lower job stress after long‐term sick leave.…”
Section: Discussionmentioning
confidence: 99%
“…Return to work is a main goal of CR in order to promote the social and psychological reintegration of heart patients (O'Hagan, Coutu, Thomas, & Mertens, 2012). Previous studies showed that patients who could successfully RTW following a cardiac event reported higher levels of emotional well-being than those who could not (Sykes et al, 2000).…”
Section: Occupational Stress and Work Adjustment After Cardiac Intervmentioning
confidence: 99%
“…The role of workplace interventions for promoting RTW has been emphasized in several studies [1,2,4-6], and the use of OH services has been specifically pointed out as beneficial [3,12,13], although the structure for such services varies greatly between countries. The present study adds an emphasis on the complexity of involving such services in employers’ RTW routines, especially within a market-based system where their involvement is based on voluntary contracts with employers.…”
Section: Discussionmentioning
confidence: 99%
“…Using OH services in rehabilitation may promote early RTW through OH service providers’ knowledge of and connection with workplaces [12,13]. While workplace-based interventions in RTW have been studied quite extensively, the use and role of OH services in such interventions has received less attention.…”
Section: Introductionmentioning
confidence: 99%